SNaPaer: A Practical Single Nucleotide Polymorphism Multiplex Assay for Genotyping of Pseudomonas aeruginosa - Eusebio, Nadia (Public Library of Science, 2013)

(untitled)
Multilocus sequence typing (MLST) represents the gold standard genotyping method in studies concerning microbial population structure, being particularly helpful in the detection of clonal relatedness. However, its applicability on large-scale genotyping is limited due to the high cost and time spent on the task. The selection of the most informative nucleotide positions simplifies genomic characterization of bacteria. A simple and informative multiplex, SNaPaer assay, was developed and genotyping of Pseudomonas aeruginosa was obtained after a single reaction of multiplex PCR amplification and mini-sequencing. This cost-effective technique allowed the analysis of a Portuguese set of isolates (n = 111) collected from three distinct hospitals and the genotyping data could be obtained in less than six hours. Point mutations were shown to be the most frequent event responsible for diversification of the Portuguese population sample. The Portuguese isolates corroborated the epidemic hypothesis for P. aeruginosa population. SNaPaer genotyping assay provided a discriminatory power of 0.9993 for P. aeruginosa, by testing in silico several hundreds of MLST profiles available online. The newly proposed assay targets less than 0.01% of the total MLST length and guarantees reproducibility, unambiguous analysis and the possibility of comparing and transferring data between different laboratories. The plasticity of the method still supports the addition of extra molecular markers targeting specific purposes/populations. SNaPaer can be of great value to clinical laboratories by facilitating routine genotyping of P. aeruginosa.